Nurses’ Knowledge, Perceived Practice, and their Associated Factors regarding Deep Venous Thrombosis (DVT) Prevention in Amhara Region Comprehensive Specialized Hospitals, Northwest Ethiopia, 2021: A Cross-Sectional Study - Senay Yohannes; Tarkie Abebe; Kidist Endalkachew; Destaw Endeshaw (Critical Care Research and Practice)
Introduction. Deep venous thrombosis is a preventable and treatable cause of death among hospitalized patients. Nurses’ knowledge and proper assessment can play a major role in improving deep venous thrombosis prevention care. Objective. To assess the knowledge, practice, and associated factors towards deep venous thrombosis prevention among nurses working at Amhara region hospitals. Methods. Institutional-based cross-sectional study was conducted among nurses working at Amhara region comprehensive specialized hospitals, Northwest, Ethiopia, from April 1 to 30, 2021. A simple random sampling technique was used to select 423 samples. A structured pretested self-administered questionnaire was used to collect data. Data were entered in epi-info version 7, analyzed using SPSS version 25, and presented by frequencies, percentages, and tables. Bivariable and multivariable logistic regression was computed, and P value < 0.05 was considered to identify statistically significant factors. Result. Good knowledge and practice of nurses towards DVT prevention were 55.6% and 48.8%, respectively. Working at the medical ward [AOR 3.175, 95% CI (1.42, 7.11)], having a BSc degree [AOR = 3.248(1.245, 8.469)], Master’s degree [AOR = 3.48, 95% CI (1.22, 9.89)], obtaining a formal training about deep venous thrombosis [AOR = 1.59; 95% CI (1.03, 2.47)], and working experience of ≥11 years [AOR = 2.11; 95% CI (1.07, 4.16)] were associated with good knowledge of nurses on the prevention of deep venous thrombosis. While having good knowledge about deep venous prevention AOR = 1.75; 95% CI (1.15, 2.65)] and working experience ≥11 years [AOR = 3.44; 95% CI (1.45, 8.13)] were significantly associated with nurses’ practice about deep venous thrombosis prevention. Conclusion. Knowledge and practice of the nurses regarding the prevention of deep venous thrombosis were found to be inadequate. Therefore, providing training, creating a conducive environment for sharing of experience, and upgrading the academic status of nurses are measures to scale up the knowledge and practice of nurses regarding deep venous thrombosis prevention.